The Effectiveness Of Techniques Of Cradle Hold And Football Hold Lowing On The Event Of Labet Milk Clothing In The Principal Mother Year 2023 - Kowi, Rut; Winarti, Eko; Mirasa, Yudied Agung (Student Scientific Journal, 2023)
Breastfeeding is the most ideal nutrition for the growth and development of infants. But usually there is a problem when mothers breastfeed their babies, which is related to improper breastfeeding techniques, which can cause blisters on the nipple. Researchers aim to find out the difference in effectiveness of thetechniques breastfeeding cradle hold and football hold on the incidence of blisters on post partum mothers at BPM Naomi In kertomananggal village, gayungan district, wonokromo district.Design of this study is the correlation with theapproach causal design.The population in this study amounted to 36 respondents with a sample size of 36 respondents. Sampling of this study uses total sampling, data collection using observation sheets. The results showed there were differences in the effectiveness of the Credle Hold technique on the incidence of blisters on nipple mothers. The majority (77.8%) of respondents withBreastfeeding Techniques Cradle Hold Against the Occurrence of Blisters on Postpartum Mothers, and a small portion (22.2%) of respondents with theBreastfeeding Technique of Football Hold Blisters.test results Chi square Breastfeeding Technique Cradle Hold Against the Occurrence of Blisters on the Mother obtained p value = 0.047 (<0.05), correlation coefficient 0.479 which means H1 is accepted or there is a relationship, while theBreastfeeding Technique Football Hold Against the Occurrence of Blisters on the Mother is obtained p value = 0.294 (> 0.05) which means there is no relationship. The conclusion of the Cradle Holdbreastfeeding technique research is more effective on the incidence of blisters on post partum mothers at BPM Sri Ani Pelem Village, Campurdarat District, Tulungagung Regency, For this reason, it is expected that postpartum mothers should use the Cradle Hold technique while breastfeeding.